QUESTIONS IN LATVIAN AND POLISH PARLIAMENTARY DEBATES: A COMPARATIVE STUDY - Chojnicka, Joanna (Lingua Posnaniensis, 2013)
This article examines the use and functions of questions in Latvian and Polish parliamentary debates from the perspective of comparative pragmatics. The research is based on a corpus of 200 utterances excerpted from transcripts of Latvian and Polish parliaments’ sittings from 2009. It uses the typology of questions in interaction developed by ILIE (1999). The paper suggests that differences in the frequency and functions of questions reflect different degrees of interactionality of a debate, which is a genre that combines monologic and dialogic features. On this basis, the discourse of Polish parliamentary debates is recognized as more interactional than its Latvian counterpart.